2013 International Conference on Control Communication and Computing (ICCC) 2013
DOI: 10.1109/iccc.2013.6731684
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for spirometric signal processing and classification by evolutionary approach and its implementation on an ARM embedded platform

Abstract: Spirometry is the most commonly performed Pulmonary Function Test (PFT) which is used to distinguish obstructive from restrictive lung diseases. This paper presents the basic system requirements for an automatic pulmonary disease classification system based on spirometric signal using a novel algorithm. The software of the system extracted features from the digitized spirogram waveform values and classified the disorders with minimum uncertainty. Classification was done by generating more data from the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the literature, we found studies that evaluated different software for the interpretation of spirometries, but none of them was a mobile app. In 2013, Nandakumar et al evaluated a software for spirometry interpretation and found an average accuracy of 95.74% [ 36 ]. More recently, in 2022, Wang et al explored the accuracy of deep learning-based analytic models based on flow-volume curves; they found that one of the models exhibited an accuracy of 95.6% when interpreting ventilatory patterns and that the physicians had an accuracy of 76.9 ± 18.4% [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we found studies that evaluated different software for the interpretation of spirometries, but none of them was a mobile app. In 2013, Nandakumar et al evaluated a software for spirometry interpretation and found an average accuracy of 95.74% [ 36 ]. More recently, in 2022, Wang et al explored the accuracy of deep learning-based analytic models based on flow-volume curves; they found that one of the models exhibited an accuracy of 95.6% when interpreting ventilatory patterns and that the physicians had an accuracy of 76.9 ± 18.4% [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed an accuracy of 97.6% when using flow-volume curves and artificial intelligence algorithms to identify normal and abnormal ventilatory patterns (Jafari et al, 2010). Moreover, some studies involving small sample size explored algorithms for PFT signal processing and classification (Veezhinathan and Ramakrishnan, 2007;Sahin et al, 2010;Nandakumar and Nandakumar, 2013). Topalovic et al (2019) developed a model to recognize normal, obstructive, restrictive, and mixed ventilatory patterns based on spirometry and lung volume test results according to the ATS/ERS guideline.…”
Section: Introductionmentioning
confidence: 99%